Tulotason vaikutuksesta elintarvikemenoihin ja kulutusmääriin - Kaarlehto, Paavo (Agricultural and Food Science, 1961)
In this study the relationships between income and food consumption are analysed on the basis of data collected for the 1956 household survey in Finland. Supported by calculation results the author indicates that in order to get reliable estimates for elasticity coefficients 1) the form of the demand function deserves special attention, especially in the case of the food items with high fat content 2) stratification of data is necessary on the basis of a) size of household and b) social class of the family. As in this case it was impossible to obtain complete sets of stratified data for proper covariance analysis, estimates for the elasticity coefficients were calculated separately from unclassified data, from data on all families with two children and from data on worker-families with two children. These elasticity coefficients, as computed in the FAO, are given in Tables 1–6 for comparision.